A unified similarity criterion and design method for geometrically distorted scale models of thin-walled hull girder structures. (November 2022) - Wang, Qinghu; Wei, Pengyu; Li, Chuntong; Wang, Deyu
Abstract: For large scale thin-walled hull girder structures, the similar scale models of them cannot​ generally satisfy an equal scale ratio between the main dimension and plate thickness. Also, when the scale models are scaled to a too small dimension, the scale models have to be further simplified by reducing the number of the stiffeners to make enough room for welding operations. The purpose of this study is to develop a unified similarity criterion and a standard design method for such geometrically distorted scale models of large scale thin-walled hull girder structures. Based on an actual 11, 4000DWT crude oil carrier hull girder structure, the proposed similarity criterion and design method was applied and validated. Numerical results show that the proposed similarity criterion and design method can guarantee a good similarity of the ultimate strength between scale models and prototype under combined loads. Also, we have derived the required condition that the proposed similarity criterion and design method can be applied to. To make a further verification of the numerical results and the proposed method, we designed and manufactured a geometrically distorted scale model for a large thin-walled box girder. A physical collapse test for the box girder was conducted to verify the reliability and accuracy of the numerical model. Highlights: Two types of geometrically distorted scale models of the thin-walled hull girder structures were proposed. A unified similarity criterion and design method for the geometrically distorted scale models of hull girder structures was proposed. The effectiveness of the proposed similarity criterion and design method was numerically verified. A collapse test was conducted for a geometrically distorted scale model of a box girder.